2014
DOI: 10.5458/jag.jag.jag-2013_004
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical Properties of Starch from Kaga Lotus Rhizome

Abstract: The lotus (Nelumbo nucifera Gaertn.) rhizome is widely cultivated and distributed in Japan. Lotuses cultivated in Japan are classified into at least ten kinds of cultivar based on their morphological characteristics. 1) Chinese lotus is a major product in Japan, with its main production area in Ibaraki Prefecture. According to criteria for vegetable cultivation from the Ibaraki Agriculture Institute 2) , Kanasumi-lines (Nos. 20 and 34) and Kohoku-No-Hikari are the major cultivars derived from the Chinese lotus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Lotus seeds, consumed boiled or processed into powder, are also used in the pharmaceutical industry to treat inflammation, arrhythmia, cancer, and skin diseases [ 7 ]. Most of the starch's diverse uses are from cultivated species [ 8 11 ], and research on the wild species is still scarce [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Lotus seeds, consumed boiled or processed into powder, are also used in the pharmaceutical industry to treat inflammation, arrhythmia, cancer, and skin diseases [ 7 ]. Most of the starch's diverse uses are from cultivated species [ 8 11 ], and research on the wild species is still scarce [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that starch granules from lotuses had vertically long oval shapes, and hilum was observed at the end of the starch granules. 5) 10) 22) 23) Visualization by polarized light microscopy showed that the starch granules exhibited a Maltese cross at the end of the starch granule ( Fig. 2 at 50 °C).…”
Section: Resultsmentioning
confidence: 98%
“…Previously, we reported that the shape of the starch derived from the Shinashirobana cultivar was slightly different from those of other lotus cultivars by optical microscopy. 5) Thus, we determined the distribution of the starch granules from the Shinashirobana cultivar and Kanasumi-line No. 20 using a laser diffraction particle analyzer.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations